Revitalization of Character Education to Overcome Moral Crisis Among Islamic Boarding School Students in Digital Era - Emier Azka, Mohammed; Syahriani, Fadilla; Amyrul Hafidz Hamam, Muhammad Azyzy; Syahnur, Lutfiah; Fajri Mulyani, Fini (Journal of Educational Management and Strategy, 2025)
This study aims to analyze the challenges of character education in Islamic boarding schools (pesantren) caused by the impact of digital technology on students’ academic performance. A mixed methods design was employed, combining qualitative interviews with teachers, students, and staff members, and quantitative surveys distributed to teachers and students. The qualitative approach explored key informants’ perspectives on integrating technology into character education, while the quantitative data were statistically analyzed to evaluate the effect of technology and provide concrete illustrations. The findings indicate that character education in pesantren becomes significantly more effective when digital tools are integrated with religious instruction. Notably, 85% of students reported a stronger understanding of moral principles when technology was used to complement religious learning, demonstrating its role in enhancing moral responsibility. However, the study also highlights limitations, particularly the regional scope and resource constraints that hinder the full application of digital technology in some institutions. The research implies that pesantren can successfully modernize their pedagogy by combining traditional religious teachings with digital innovation without compromising moral and religious values. These findings offer practical guidance for teachers and administrators to adapt their instructional approaches in the digital age. Future research is recommended to investigate the long-term effects of this methodology on students’ moral and ethical development.